Myasthenia Gravis and Abdominal Aortic Aneurysm: A Rare Combination - Papadoulas, Spyros; Zotou, Anastasia; Kouri, Natasa; Tsimpoukis, Andreas; Zampakis, Petros; Koutsogiannis, Nikolaos; Chroni, Elisabeth (AORTA, 2023)
Abdominal aortic aneurysm in a patient with myasthenia gravis (MG) is extremely rare. We present a 64-year-old male with MG and an asymptomatic abdominal aortic aneurysm treated endovascularly. After extubation, he suffered a cardiac arrest due to an acute myocardial infarction. Cardiopulmonary resuscitation and a primary coronary angioplasty led to a satisfactory outcome. Special care is needed due to higher rates of postoperative complications in these patients.
Keywords: myasthenia gravis; abdominal aortic aneurysm; endovascular abdominal aneurysm repair; acetylcholine receptor